Advances in new drug therapies for the management of sickle cell disease. (4th May 2018) - Ataga, Kenneth I.; Desai, Payal C.
ABSTRACT: Introduction : Sickle cell disease (SCD) is an orphan disease in the United States, but is highly prevalent worldwide. Only two drugs, hydroxyurea and L-glutamine, are approved for this disease. With an improved understanding of the pathophysiology of SCD as well as the success of several recently approved drugs for other orphan diseases, there is an increased interest in the development of drugs for SCD. Areas covered : This review summarizes published studies of drug therapies and ongoing trials of novel agents. Expert opinion : The development of drugs with different mechanisms of action offers opportunities for combination and individualized therapy in SCD. In addition to acute pain crisis, the evaluation of other SCD-related complications, exercise capacity, patient reported outcomes and validated surrogate endpoints are necessary to advance drug development. It is important to involve sites in sub-Saharan Africa and India, which have the highest burden of SCD, in trials of novel therapies.